2012
DOI: 10.1111/j.1750-3841.2012.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Galactooligosaccharides and Modified Waxy Maize Starch on Some Attributes of Yogurt

Abstract: This study examined the influence of galactooligosaccharides (GOS) and modified waxy maize starch (MWMS) addition on the growth of starter cultures, and syneresis and firmness of low-fat yogurt during storage for 28 d at 4 °C. The control yogurt (CY) was prepared without any prebiotics. Incorporation of 2.0% (w/v) GOS improved the growth of L. delbrueckii ssp. bulgaricus ATCC 11842 resulting in a shorter fermentation time. There was a significant (P < 0.05) increase in proteolysis in yogurt made with GOS (GOSY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…Ramchandran and Shah (2009) reported that high-performance inulin, as a prebiotic, significantly stimulated the growth of ST 1275 in RSM containing 1% high-performance inulin (high-performance inulin/RSM, wt/vol), which may be because of the production of extracellular enzymes that could hydrolyze long-chain fructans with additional formation of fructose. For other prebiotics such as modified waxy maize starch and galactooligosaccharides, Prasad et al (2013) reported that 2% additional galactooligosaccharides or modified waxy maize starch significantly (P < 0.05) improved the viability of L. delbrueckii ssp. bulgaricus and Strep.…”
Section: Composition Of Pepsmentioning
confidence: 97%
See 2 more Smart Citations
“…Ramchandran and Shah (2009) reported that high-performance inulin, as a prebiotic, significantly stimulated the growth of ST 1275 in RSM containing 1% high-performance inulin (high-performance inulin/RSM, wt/vol), which may be because of the production of extracellular enzymes that could hydrolyze long-chain fructans with additional formation of fructose. For other prebiotics such as modified waxy maize starch and galactooligosaccharides, Prasad et al (2013) reported that 2% additional galactooligosaccharides or modified waxy maize starch significantly (P < 0.05) improved the viability of L. delbrueckii ssp. bulgaricus and Strep.…”
Section: Composition Of Pepsmentioning
confidence: 97%
“…The firmness kept increasing for all FM samples during refrigerated storage. Prasad et al (2013) Hassan (2008) reported that high-molecular-mass EPS has the ability to strengthen the firmness of the network by interacting with other milk constituents. Our results showed that FM with added PEPS had higher syneresis and also higher firmness and gumminess compared with those of FM-ST 1275 and FM-ST 1303, which may be caused by the high-molecular-mass PEPS added in FM.…”
Section: Texture Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…These values corroborate with those of the present study, where the fermented rice extract without WMS showed syneresis of 10.16 g 100 g -1 and with 4 g 100 g -1 WMS, 7.51 g 100 g -1 , measured after 48 h of preparation, and food matrices were totally different since those authors worked with yogurt from reconstituted cow's milk. Prassad et al (2013), working with yogurt added of 2 g 100 g -1 of modified WMS after one day of preparation, obtained respectively, 3.66 and 3.54 g 100 g -1 with approximately 3% reduction in the syneresis index, concluding that the modified WMS contributed to reduce the water loss by the gel network in the product. In this study, fermented rice extract containing 4 g 100 g -1 WMS presented a reduction of 26% over the fermented rice extract without WMS, difference that might be associated with the use of a non-dairy base, as well as the higher amount of WMS.…”
Section: Syneresis and Physico-chemical Characteristicsmentioning
confidence: 99%
“…Then, a reduction of total soluble sugars levels and increase of total acidity occurred when increasing WMS ( Figure 1B, C). This trend can be explained by the metabolism of inoculated microorganisms that used sugars and WMS for the production of acids such as lactic, the SCFA and acetic, among others, causing increase in total acidity and decrease in total soluble sugars (Prassad et al, 2013). Coda et al (2012), working with fermented beverages "yogurt type" obtained from various cereals, observed in the sample made of rice flour sweetened with 10 g 100 g -1 of concentrated grape must, levels of sugars (glucose and fructose) of 5.61 g 100 g -1 , lower than those found in our study, where the minimum was 8.73 g 100 g -1 (fermented rice extract containing 16 g 100 g -1 WMS), due to the addition of 10 g 100 g -1 of sucrose in all elaborated extracts.…”
Section: Syneresis and Physico-chemical Characteristicsmentioning
confidence: 99%